C1‐inhibitor efficiently inhibits Escherichia coli‐induced tissue factor mRNA up‐regulation, monocyte tissue factor expression and coagulation activation in human whole blood. (4th July 2013) - Landsem, A.; Nielsen, E. W.; Fure, H.; Christiansen, D.; Ludviksen, J. K.; Lambris, J. D.; Østerud, B.; Mollnes, T. E.; Brekke, O.‐L.
Summary Both the complement system and tissue factor (TF), a key initiating component of coagulation, are activated in sepsis, and cross‐talk occurs between the complement and coagulation systems. C1‐inhibitor (C1‐INH) can act as a regulator in both systems. Our aim in this study was to examine this cross‐talk by investigating the effects of C1‐INH on Escherichia coli‐induced haemostasis and inflammation. Fresh human whole blood collected in lepirudin was incubated with E. coli or ultrapurified E. coli lipopolysaccharide (LPS) in the absence or presence of C1‐INH or protease‐inactivated C1‐INH. C3 activation was blocked by compstatin, a specific C3 convertase inhibitor. TF mRNA was measured using reverse transcription–quantitative polymerase chain reaction (RT–qPCR), and TF surface expression was measured by flow cytometry. In plasma, the terminal complement complex, prothrombin F1·2 (PTF1·2) and long pentraxin 3 (PTX3) were measured by enzyme‐linked immunosorbent assay (ELISA). Cytokines were analysed using a multiplex kit. C1‐INH (1·25–5 mg/ml) reduced both LPS‐ and E. coli‐induced coagulation, measured as a reduction of PTF1·2 in plasma, efficiently and dose‐dependently (P < 0·05). Both LPS and E. coli induced marked up‐regulation of TF mRNA levels and surface expression on whole blood monocytes. This up‐regulation was reduced efficiently by treatment with C1‐INH (P < 0·05). C1‐INH reduced the release of PTX3 (P < 0·05) and virtually all cytokines measured (P < 0·05). Complement activation was inhibited more efficiently with compstatin than with C1‐INH. C1‐INH inhibited most of the other readouts more efficiently, consistent with additional non‐complement‐dependent effects. These results indicate that complement plays a role in activating coagulation during sepsis and that C1‐INH is a broad‐spectrum attenuator of the inflammatory and haemostatic responses.